PAUD Teachers' Speaking Skill in Teaching English in Tampan District - SYAIFULLAH SYAIFULLAH; Refika Andriani; M. Fadhly Farhy Abbas (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2020)
The aim of this research is to describe about PAUD teachers’ speaking skill in Tampan district. The method of this research was survey design, there was no treatment and data manipulating on that research variable, independent variable, its only describe the result of PAUD teachers’ speaking skill in teaching English in Tampan district Pekanbaru. This research data was collected by using a test, speaking. Scientifically, the result of PAUD teachers’ speaking skill has been known. Their speaking skill in teaching English was low. It was 33.5 on poor level. The result showed that the teachers should improve their skill in teaching English. Besides, this research result is expected to be as one of references in deciding the method, media, or resources to be applied in teaching English for early childhood students. In conclusion, PAUD teachers in Tampan district seldom use or practice their English whether with their colleague or students.